Pinealitis accompanying equine recurrent uveitis. - Kalsow, C M (1993)
There is no direct verification of pineal gland involvement in human uveitis. Specimens of pineal tissue are not available during active uveitis in human patients. Naturally occurring uveitis in horses gives us an opportunity to examine tissues during active ocular inflammation. We examined the pineal gland of a horse that was killed because it had become blind during an episode of uveitis. The clinical history and histopathology of the eyes were consistent with post-leptospiral equine recurrent uveitis. The pineal gland of this horse had significant inflammatory infiltration consisting mainly of lymphocytes with some eosinophils. This observation of pinealitis accompanying equine uveitis supports the animal models of experimental autoimmune uveoretinitis with associated pinealitis and suggests that the pineal gland may be involved in some human uveitides.